2013
DOI: 10.1088/0953-4075/46/22/224005
|View full text |Cite
|
Sign up to set email alerts
|

Jaynes–Cummings theory out of the box

Abstract: We report new results in neoclassical quantum optics by applying the central theme of the Jaynes–Cummings paper of 1963. This theme, which Jaynes and Cummings emphasized in several ways, is the key role that must be assigned to radiative back reaction in quantum radiation dynamics. Its consequences are well known in subjects related to cavity quantum electrodynamics, and its influence on optical pulse evolution theory is equally strong. Here we provide a new solitonic extension of the radiation reaction theme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…This is the same result as the one obtained when superimposing a type 1 and a type 2 first order solution except that the sign of the displacement is inverted, and so the imprint is moved to the right. This has already been shown in [24,25].…”
Section: A Backward-transfer Solutionsupporting
confidence: 64%
See 2 more Smart Citations
“…This is the same result as the one obtained when superimposing a type 1 and a type 2 first order solution except that the sign of the displacement is inverted, and so the imprint is moved to the right. This has already been shown in [24,25].…”
Section: A Backward-transfer Solutionsupporting
confidence: 64%
“…Here, we wrote the Darboux parameter as λ a = i/τ a , with τ a ∈ R which makes it easier to associate it to a physical quantity, namely, the duration of the pulses. Two possible solutions arising from this have already been thoroughly studied by Groves, Clader and Eberly [24] so we will just summarize the results that we will need. Table 1 contains all the elements of the involution M a for the three first order solutions that are going to be considered.…”
Section: First Order Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…5. Additionally, as long as the signal pulse is only stored in one channel, we can displace the imprint and retrieve it (if we consider a finite medium) by the results already obtained for a Λ system [25,26]. It is also interesting to note that, together with the displacement of the imprint, the intensity of the control pulses is inverted (see Fig.…”
Section: Two-channel Memorymentioning
confidence: 84%
“…Recent research has shown how the interaction of broadband pulses with matter opens the door to high-speed switching. In this framework, it has been shown that storage, manipulation and retrieval of a signal pulse in a Λ system is possible [25] even in non-idealized conditions [26] and how the methodology presented there can be extended to accommodate the storage of multiple pulses and added control of the information stored [27]. A generalized two-pulse area was shown to play a role [28]:…”
Section: Introductionmentioning
confidence: 99%